The role of sport activity in achieving Psychological stiffness. a case study - كواش , منيرة (sports creativity, 2025)
Introduction: The adolescence stage is one of the most important stages of growth that requires special needs that contribute to the formation and stability of the personality of the adolescent and achieve mental health. Psychological stiffness is one of the fundamental variables that reflect a range of personality traits that limit the unhealthy effects of various pressures Types. Psychological rigidity (stiffness) is a commitment to the values and goals of life towards oneself and others, with a sense of control over the course of life and the challenge of life. In our study, we wanted to know whether regular physical activity practiced by adolescents had a role in achieving Psychological stiffness. Methods/Methodology: The approach of research is the case study method it is a comprehensive qualitative method based on the accurate and comprehensive description of the cases. Research tools: interview and the measure of the Psychological stiffness of Dr Tanhid Adel Fadel. Results & Discussion: the study has shown that the level of psychological stiffness in adolescent sports practicing was law Conclusion: The study has recommended that educators and coaches in particular should establish guidance programs to promote the concept of psychological stiffness and the affecting factors.